Understanding the Facilitators and Barriers to COVID-19 Vaccine Uptake Among Teachers in the Sagnarigu Municipality of Northern Ghana: A Cross-Sectional Study - Dubik SD (Dove Medical Press, 2022)
Stephen Dajaan Dubik Department of Public Health, Catholic University College of Ghana, Fiapre, GhanaCorrespondence: Stephen Dajaan Dubik, Email stephendubik@gmail.comPurpose: This research aims to identify facilitators and barriers to COVID-19 vaccination intention and uptake among teachers in the Sagnarigu Municipality of Ghana.Methods: The survey collected quantitative data from the teachers using a cross-sectional study design. Logistic regression analysis was used to identify facilitators and barriers to COVID-19 vaccination.Results: The teachers' (N = 421) COVID-19 vaccination intention before rollout, after rollout, and actual uptake were 49%, 63%, and 11%, respectively. In a multiple regression analysis, key facilitators of intention were vaccinated against hepatitis B (AOR: 2.5, 95 CI: 1.03, 4.93), willingness to recommend COVID-19 vaccine to students (AOR: 4.78,95% CI: 1.95, 11.70), adequacy of information about the expectation of the COVID-19 vaccine (2.42, 95% CI: 1.04, 5.56), and the disbelief that COVID-19 vaccine will cause illness (AOR: 2.50, 95% CI: 1.16, 5.33). Unconfident in the COVID-19 vaccine (AOR: 0.01, 95% CI: 0.001, 0.118), perception of not being susceptible to COVID-19 (AOR: 0.38, 95% CI: 0.17, 0.88), and feeling uncomfortable getting the vaccine (AOR: 0.17, 95% CI: 0.08, 0.38) were barriers to COVID-19 vaccination intention. Key facilitators of COVID-19 vaccine uptake were being a Christian (AOR: 3.63, 95% CI: 1.60, 8.24), teaching in the Senior High School (SHS)/technical (AOR: 13.43, 95% CI: 1.90, 9.48). Barriers to the vaccine uptake were uncomfortable getting the vaccine (AOR: 0.06, 95% CI: 0.06, 0.49), disbelief that vaccinating teachers will reduce school absenteeism (AOR: 0.45, 95% CI: 0.18, 1.07), unconfident in the COVID-19 vaccine (AOR: 0.45, 95 CI: 0.18, 1.07), and unavailability of the COVID-19 vaccine.Conclusion: Facilitators and barriers to COVID-19 vaccination are multifaceted, including sociodemographic, health beliefs, and contextual factors. Addressing the obstacles to COVID-19 vaccination is crucial for adequate COVID-19 vaccine coverage among teachers in Ghana.Keywords: COVID-19 vaccination, barriers, vaccine uptake, school health, teachers, Ghana